Effect of mooring system on moored ship motions and harbour tranquillity. (15th April 2008) - Sakakibara, Shigeki; Kubo, Masayoshi
Recently, numerical simulation on the motions of ship moored in ports and harbours is carried out to evaluate property of the motions, and is applied to calculating harbour tranquillity directly. However, the simulations take much time, costs and knowledge on evaluation of the results. In this paper, we propose simple graphs for estimating the moored ship motions and mooring loads by a simple index: 'asymmetrical parameter', which is derived from ratio of spring constants between fenders and mooring lines, and demonstrate an evaluation method on harbour tranquillity and effect of the fender type (pneumatic or buckling types) on it.